Reducing medicine-induced deterioration and adverse reactions (ReMInDAR) trial: study protocol for a randomised controlled trial in residential aged-care facilities assessing frailty as the primary outcome. Issue 4 (22nd April 2020) - Lim, Renly; Bereznicki, Luke; Corlis, Megan; Kalisch Ellett, Lisa M; Kang, Ai Choo; Merlin, Tracy; Parfitt, Gaynor; Pratt, Nicole L; Rowett, Debra; Torode, Stacey; Whitehouse, Joseph; Andrade, Andre Q; et al.
Abstract : Introduction: Many medicines have adverse effects which are difficult to detect and frequently go unrecognised. Pharmacist monitoring of changes in signs and symptoms of these adverse effects, which we describe as medicine-induced deterioration, may reduce the risk of developing frailty. The aim of this trial is to determine the effectiveness of a 12-month pharmacist service compared with usual care in reducing medicine-induced deterioration, frailty and adverse reactions in older people living in aged-care facilities in Australia. Methods and analysis: The reducing medicine-induced deterioration and adverse reactions trial is a multicentre, open-label randomised controlled trial. Participants will be recruited from 39 facilities in South Australia and Tasmania. Residents will be included if they are using four or more medicines at the time of recruitment, or taking more than one medicine with anticholinergic or sedative properties. The intervention group will receive a pharmacist assessment which occurs every 8 weeks. The pharmacists will liaise with the participants' general practitioners when medicine-induced deterioration is evident or adverse events are considered serious. The primary outcome is a reduction in medicine-induced deterioration from baseline to 6 and 12 months, as measured by change in frailty index. The secondary outcomes are changes in cognition scores, 24-hour movement behaviour, grip strength, weight, percentage robust, pre-frail and frail classification, rate of adverse medicine events, health-related quality of life and health resource use. The statistical analysis will use mixed-models adjusted for baseline to account for repeated outcome measures. A health economic evaluation will be conducted following trial completion using data collected during the trial. Ethics and dissemination: Ethics approvals have been obtained from the Human Research Ethics Committee of University of South Australia (ID:0000036440) and University of Tasmania (ID:H0017022). A copy of the final report will be provided to the Australian Government Department of Health. Trial registration number: Australian and New Zealand Trials Registry ACTRN12618000766213.